SURVEI TINGKAT KEMAMPUAN TEKNIK DASAR DAN KONDISI FISIK PADA SISWA SEKOLAH SEPAK BOLA (SSB) RANTAI BAJA KOTA PURWODADI TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this research was to determine the basic engineering and the physical condition of the student School Football ( SSB ) Ratai Steel in 2013 . This study uses the basic techniques of test instruments soccer skills . Descriptive results of calculations known percentage of students overall physical condition of the school football ( SSB ) Steel Chain , it can be concluded that the overall physical condition of the football school students ( SSB ) Steel Chain In 2013 most of the 60 ( 60 % ) of students included in the medium category . To test the level of basic engineering skills football soccer school students ( SSB ) Steel Chain in 2013 note that 74 ( 74 % ) of students included in both categories . The conclusions of this study is the overall physical condition of the football school students ( SSB ) Steel Chain city Purwodadi most 60 students ( 60 % ) included in the medium category , 38 students ( 38 % ) included in both categories , 2 students ( 2 % ) included in the category of less and no students were included in both categories once and less so . To test the basic movement skills soccer soccer school students ( SSB ) Steel Chain Purwodadi town is known that 74 ( 74 % ) of students included in either category , 26 ( 26 % ) of students included in the category of moderate and no students are included in the category of less